Mensagens cifradas: a construção de linguagens diagramáticas - Borges, Priscila Monteiro (2010)
When the verbal language becomes an actual written text, it acquires particular qualities from the visual language system. Therefore, it becomes necessary to investigate the representative power of a visual form in a verbal written text. The verbal written system visuality combine two writing functions: the communicative function and the visual poetics. The first characterizes the verbal system, and it is also present on the oral verbal language. The second is a particular quality from written systems expressed on calligraphy and typography. In order to investigate the representative function of the visual aspects on the verbal written text, we selected some typefaces that modify the letter shape, making it difficult to read. These typefaces emphasize the text visuality and create its own way to communicate visually; written with them, the verbal text starts to communicate visually as well. The visual form communicability of these typefaces is revealed by semiotic analysis of them, considering both the form of each character and the texts written with them. To analyze the sign communicative process, we adopted Peirce s semiotic. This theory was developed as a philosophical discipline composed of a classification model that logically indicates all the possible semioses. Having a general logical structure, Peirce s semiotic can be applied to any sign. Its classification model is grounded on continuity and relation of categories, which express the enchainment of different sign aspects. Although Peirce s semiotic has these qualities, many semiotic applications use the sign classes as they were a tight classification to which the sign might fit, turning it into a formalist theory. To avoid this problem we created our own method of analysis, which is based on a visual model, also proposed by us, that emphasizes the continuity and the dynamics of the sign process. This method is based on the 66 classes of sign, which is not well known and which is poorly explored, because it was only suggested by Peirce. This classification reveals a complex set of related classes that must be carefully analyzed. The 66 classes show an extensive gradation between classes, consequently emphasizing the continuity of the sign process. For these reasons, we were convinced that this system had an analytical power that could be explored. Despite the difficult problems and controversial topics, we decided to create a method of analysis with it and to dedicate a large amount of time working on this theory. Consequently, this research has two branches: one dedicated to the theoretic studies and to the development of the analytical method; the other, devoted to the application of the method, aiming to reveal the representative power of the visual forms on verbal written texts